The Method of Optimum Secondary Frequency Regulating and Power - Kostiuk, V. O.; Sidorov, O. F. (Visnyk of Vinnytsia Politechnical Institute, 2017)
There have been presented the conditions under which the technical and economic parameters of the processes of secondary frequency and power regulation in the electric power system (EPS) can be close to optimal. It has been shown that in order to fulfill these conditions it is sufficient to maintain the gain of the system of secondary automatic frequency and power control according to the frequency deviation at the level of the numerical value of EPS stiffness factor with respect of frequency.